(untitled) (Birat Journal of Health Sciences, 2025)
Introduction : Complementary feeding is essential for growth and development during early childhood, particularly between 6 months and 2 years of age, when breast milk alone can no longer meet nutritional needs. In Nepal, suboptimal complementary feeding practices continue to contribute to child undernutrition, making it important to understand mothers’ knowledge, attitudes, and practices (KAP) in the local context. This study aimed to assess the KAP of mothers regarding complementary feeding and describe their socio-demographic profile attending Birat Medical College Teaching Hospital. Methods : A descriptive cross-sectional study was conducted among 214 mothers of children aged 6 months to 2 years attending the pediatric outpatient clinic. Participants were selected through convenience sampling. Data were collected using a structured, interviewer-administered questionnaire based on WHO Infant and Young Child Feeding guidelines. Descriptive statistics were applied and results were presented as frequencies and percentages. Results: Most mothers were aged 20–29 years (62.6%), educated up to higher secondary or college level (36.4%), and predominantly housewives (68.2%). A total of 61.2% correctly identified 6 months as the appropriate age to begin complementary feeding. Attitudes were largely positive, with 87.4% considering complementary feeding very important and 69.2% agreeing that exclusive breastfeeding for the first 6 months is sufficient. In practice, 48.1% initiated complementary feeding at exactly 6 months, and 46.7% reported feeding their child three times daily. Common foods included fruits (58.9%), rice porridge (38.3%), and boiled eggs (38.3%). Hygiene practices were generally satisfactory, with 72% washing hands before preparing food. Additionally, 66.8% had sought healthcare advice on feeding, mainly from doctors (61.7%). Conclusion : Mothers demonstrated generally positive attitudes and moderate knowledge regarding complementary feeding, although deviations from recommended feeding practices were evident. Strengthening routine counselling and community-based nutrition education may help bridge remaining gaps and promote optimal complementary feeding behaviours in this population.